If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6 = 6x + 9 + -7x Reorder the terms: 6 + 3x = 6x + 9 + -7x Reorder the terms: 6 + 3x = 9 + 6x + -7x Combine like terms: 6x + -7x = -1x 6 + 3x = 9 + -1x Solving 6 + 3x = 9 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 6 + 3x + x = 9 + -1x + x Combine like terms: 3x + x = 4x 6 + 4x = 9 + -1x + x Combine like terms: -1x + x = 0 6 + 4x = 9 + 0 6 + 4x = 9 Add '-6' to each side of the equation. 6 + -6 + 4x = 9 + -6 Combine like terms: 6 + -6 = 0 0 + 4x = 9 + -6 4x = 9 + -6 Combine like terms: 9 + -6 = 3 4x = 3 Divide each side by '4'. x = 0.75 Simplifying x = 0.75
| -5a+7+4a=-(a+7) | | F(x)=2(x^2-9x+5)-5(x-k) | | n+40=41 | | -5a-7+4a=-(a+7) | | 6x-5=x^2+4 | | Y=sqrt(x-4)+5 | | 2x+3x=1000 | | 2x+80=152 | | n+12=13n | | x=4509307201 | | -7x=-154 | | n+8-n=9n-n | | 5a+7-4a=-(a+7) | | 5+-1v+4v=1+5v+3 | | n+8=9n | | -5a+7-4a=-(a+7) | | -3x^2-10x+5=0 | | 6x=-14x | | -105+8x+6x^2+x^3=0 | | 4x^2+8x=38-6y^2 | | 2xy*3-60+x=6xy*10 | | -(-15x)-3= | | xy=3x^2-6+y | | 9x+4x-6x-5=2 | | 108=12X^2 | | 3x+5x-6x-5=5 | | mx+4=3x-n | | 2x+9x-7x-5= | | p-8=24 | | e^5x+6=8e^3x | | 4sin^4x-1=0 | | 7(8x+2y)= |